Molten Sn solvent expands liquid metal catalysis - Junma Tang; Nastaran Meftahi; Andrew J. Christofferson; Jing Sun; Ruohan Yu; Md. Arifur Rahim; Jianbo Tang; Guangzhao Mao; Torben Daeneke; Richard B. Kaner; Salvy P. Russo; Kourosh Kalantar-Zadeh (Nature Communications)
Abstract Regulating favorable assemblies of metallic atoms in the liquid state provides promise for catalyzing various chemical reactions. Expanding the selection of metallic solvents, especially those with unique properties and low cost, enables access to distinctive fluidic atomic structures on the surface of liquid alloys and offers economic feasibility. Here, Sn solvent, as a low-cost commodity, supports unique atomic assemblies at the interface of molten SnIn0.1034Cu0.0094, which are highly selective for H2 synthesis from hydrocarbons. Atomistic simulations reveal that distinctive adsorption patterns with hexadecane can be established with Cu transiently reaching the interfacial layer, ensuring an energy-favorable route for H2 generation. Experiments with a natural oil as feedstock underscore this approach’s performance, producing 1.2 × 10− 4 mol/min of H2 with 5.0 g of catalyst at ~93.0% selectivity while offering reliable scalability and durability at 260 °C. This work presents an alternative avenue of tuning fluidic atomic structures, broadening the applications of liquid metals.